2018
DOI: 10.1051/e3sconf/20184500109
|View full text |Cite
|
Sign up to set email alerts
|

Water in the city. The development of permeable surfaces in urban areas

Abstract: In the coming years, cities will face new challenges from a rapidly changing climate. Many physical infrastructure and building projects will face new or more severe risks from extreme flooding, precipitation and heat events. At the same time, environmental conditions are also projected to change, posing chronic hazards as average yearly temperatures rise. The natural cycle of water circulation in contemporary cities is often very disturbed as a result of improper management of space. The necessity to protect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In Jopek's study carried out in Cracow, she showed the potential to increase the absorption capacity of identified sites. The results presented by the researcher revealed a clear underestimation of the size of the existing open areas in relation to the required share of biologically active areas on the basis of local spatial development plans or decisions on land development conditions [24].…”
Section: Problems and Inaccuracies In Planning Provisionsmentioning
confidence: 91%
“…In Jopek's study carried out in Cracow, she showed the potential to increase the absorption capacity of identified sites. The results presented by the researcher revealed a clear underestimation of the size of the existing open areas in relation to the required share of biologically active areas on the basis of local spatial development plans or decisions on land development conditions [24].…”
Section: Problems and Inaccuracies In Planning Provisionsmentioning
confidence: 91%